The first accurate and precise calendar dating of New Zealand Māori Pā, using Otāhau Pā as a case study. (April 2017) - Hogg, Alan; Gumbley, Warren; Boswijk, Gretel; Petchey, Fiona; Southon, John; Anderson, Atholl; Roa, Tom; Donaldson, Lloyd
Abstract: This research investigates the potential of radiocarbon wiggle-match dating of palisade posts to provide precise and accurate calendar ages for Māori pā (forts), using Otāhau Pā in the inland Waikato region, New Zealand, as a case study. Even though pā are a dominant element of the pre-European North Island archaeological landscape, they are poorly understood archaeologically, with systematic investigations hampered by the relative lack of precision in radiocarbon dating within the context of New Zealand's comparatively short prehistory. Using the Southern Hemisphere calibration curve SHCal13, we determine wiggle-match calibrated ages for three palisade posts, using different sampling resolutions to determine the cost-effectiveness of the method. We also test the accuracy of the wiggle-match by obtaining new Southern Hemisphere calibration data from known calendar-age kauri.